2002
DOI: 10.1046/j.1464-410x.2002.02743.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for superficial bladder cancer under local anaesthetic

Abstract: Objectives To evaluate the use of local anaesthesia (LA) in 5-aminolaevulinic acid (ALA) photodynamic therapy (PDT) for superficial transitional cell carcinoma (TCC) of the bladder, and to provide further toxicity and tolerability data on this new method within the context of a phase 1 trial. Patients and methods ALA PDT was administered to 19 patients with recurrent superficial TCC (stage Ta/carcinoma in situ, grades 1-3) using escalating doses of ALA (3-6%) and 633 nm laser light (25-50 J/cm 2 ) under variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 37 publications
0
30
0
1
Order By: Relevance
“…In this respect, SCCs appear similar in their PDT response to other carcinoma types, such as diverse (Corti et al 1995), colon carcinoma (Piot et al 2001), and bladder carcinoma (Shackley et al 2002). ALA-PDT in these tumours is subject to both experimental and clinical investigation (Biel 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, SCCs appear similar in their PDT response to other carcinoma types, such as diverse (Corti et al 1995), colon carcinoma (Piot et al 2001), and bladder carcinoma (Shackley et al 2002). ALA-PDT in these tumours is subject to both experimental and clinical investigation (Biel 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not focus on local anesthesia use, it is suggestive of its positive impact on patient satisfaction. Shackley et al [3] have also evaluated the feasibility of photodynamic therapy for superficial bladder cancer under various local lignocaine anesthesia protocols. The investigators concluded that this certain approach offers a satisfactory alternative to conventional methods with sufficient pain management demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…VAS is an already used pain-quantification strategy, which although not completely reliable, is at least sufficiently standardized to enable ''objective measurements''. Others [3,5] have used identical or similar methods for pain assessment in similar settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although encouraging oncological results, PDT was abandoned due to side effects such as skin sensitisation and bladder shrinking 7 . With the venue of ALA or derivatives thereof, which are administered intravesicaly and have better tumor specificity as opposed to muscle, interest for PDT in bladder cancer treatment has regained interest [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%